PENGARUH MODEL JIGSAW BERBANTUAN FLASHCARD TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 5 KAWAN - Ni Luh Pande Ayu Erna Wati; I Gusti Ngurah Triyana; I Komang Wisnu Budi Wijaya (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT This study was motivated by the low Science and Social Studies (IPAS) learning outcomes of fifth-grade students at SD Negeri 5 Kawan Bangli, which were caused by the use of conventional teaching methods and the lack of interactive learning media. The purpose of this study was to determine the effect of the Jigsaw-type cooperative learning model assisted by flashcard media on the IPAS learning outcomes of fifth-grade students at SD Negeri 5 Kawan Bangli. This research employed a quantitative approach with a quasi-experimental design using the nonequivalent control group design. The population consisted of all fifth-grade students of SD Negeri 5 Kawan Bangli in the 2025/2026 academic year. The sample included Class VA as the experimental group and Class VB as the control group, with a total of 59 students. Data were collected using an objective multiple-choice test on the topic of light and its properties. The data were analyzed using descriptive statistics and hypothesis testing. The results indicated that the implementation of the Jigsaw-type cooperative learning model assisted by flashcard media had a significant effect on students’ IPAS learning outcomes, with the experimental group achieving higher learning outcomes than the control group. Therefore, the Jigsaw-type cooperative learning model assisted by flashcard media can be considered an effective alternative instructional approach for improving elementary school students’ IPAS learning outcomes. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar IPAS siswa kelas V di SD Negeri 5 Kawan Bangli yang disebabkan oleh penggunaan model pembelajaran konvensional dan kurangnya media pembelajaran interaktif. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran kooperatif tipe jigsaw berbantuan media flashcard terhadap hasil belajar IPAS siswa kelas V di SD Negeri 5 Kawan Bangli. Penelitian ini merupakan penelitian kuantitatif dengan jenis quasi experiment menggunakan rancangan nonequivalent control group design. Populasi penelitian adalah seluruh siswa kelas V SD Negeri 5 Kawan Bangli tahun ajaran 2025/2026. Sampel penelitian terdiri dari kelas VA sebagai kelas eksperimen dan kelas VB sebagai kelas kontrol dengan jumlah total 59 siswa. Pengumpulan data dilakukan menggunakan tes objektif berbentuk pilihan ganda pada materi cahaya dan sifatnya. Data dianalisis menggunakan statistik deskriptif dan uji hipotesis. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran kooperatif tipe jigsaw berbantuan media flashcard berpengaruh signifikan terhadap hasil belajar IPAS siswa, dengan hasil belajar kelas eksperimen lebih tinggi dibandingkan kelas kontrol. Dengan demikian, model pembelajaran kooperatif tipe jigsaw berbantuan media flashcard dapat dijadikan alternatif pembelajaran yang efektif untuk meningkatkan hasil belajar IPAS siswa sekolah dasar.